2014
DOI: 10.4028/www.scientific.net/amr.975.243
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Property of MgMoO<sub>4</sub> Crystals

Abstract: In this work, we report on the synthesis of MgMoO4 crystals by oxide mixed method. The powder was calcined at 1100 °C for 4h and analyzed by X-ray diffraction (XRD), Fourier transform infrared (FT-IR), Field emission gun scanning electron microscopy (FEG-SEM), Ultraviolet-visible (UV-vis) absorption spectroscopy and Photoluminescence (PL) measurement. XRD analyses revealed that the MgMoO4 powders crystallize in a monoclinic structure and are free secondary phases. UVvis technique was employed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The MgSpray spherical nanoparticles were changed from spherical shape to become faceted particles, mainly in the Mg1000 sample (Figure d). Xavier et al observed similar morphology in synthesized MgMoO 4 by the solid-state method at 1100 °C for 4 h. The heat treatment favored the diffusion and sintering processes caused the growth of these particles.…”
Section: Resultsmentioning
confidence: 81%
“…The MgSpray spherical nanoparticles were changed from spherical shape to become faceted particles, mainly in the Mg1000 sample (Figure d). Xavier et al observed similar morphology in synthesized MgMoO 4 by the solid-state method at 1100 °C for 4 h. The heat treatment favored the diffusion and sintering processes caused the growth of these particles.…”
Section: Resultsmentioning
confidence: 81%
“…5. The optical, spectroscopic [27,[34][35][36][37][38][39] and some other [40][41][42] properties of undoped MgMoO 4 have been extensively studied at this moment. Some data are also available in the literature on the spectroscopic properties of MgMoO 4 crystals and powders or nanoparticles doped with Yb 3+ [27,43], Cr 3+ [40,44], Tm 3+ [31], Eu 3+ [45,46], Eu 3+ , Dy 3+ [47] and Eu 3+ ,Bi 3+ [48] ions/ion pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Some data are also available in the literature on the spectroscopic properties of MgMoO 4 crystals and powders or nanoparticles doped with Yb 3+ [27,43], Cr 3+ [40,44], Tm 3+ [31], Eu 3+ [45,46], Eu 3+ , Dy 3+ [47] and Eu 3+ ,Bi 3+ [48] ions/ion pairs. The results of these studies have shown that MgMoO 4 is interesting for applications in scintillators [27,34], phosphors [37,46,49] and laser hosts [31,40]. Along with that, the MgMoO 4 powder is widely used as a catalyst for the dehydrogenation of saturated hydrocarbons [50,51].…”
Section: Introductionmentioning
confidence: 99%